DUKUNGAN SOSIAL DAN RESILIENSI DIRI PADA GURU SEKOLAH DASAR - Zarina Akbar; Oliver Tahoma (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
This study aimed to examined the relationship between social support and resilience among elementary school teacher. This study use a correlational quantitative approach to determined the relationship. A total of 100 teacher were participating in this study, and gathered using a purposive sampling technique. Data were collected using Multidimensional Scale of Perceived Social Support (MSPSS) and Resiliencce Quotient Test. Pearson Product Moment with SPSS version 16.0 was used to test the hypothesis of the study. The results show that, r=0,706; p = 0,000 < 0,05. This results suggested that there is a significant relationship with positive concentration between social support and resilience among elementary school teacher.